Mechanism and Efficacy Analysis of Minocycline Hydrochloride Combined with Metronidazole in the Treatment of Periodontitis - Wang, Xiaohan (Exploring Science Academic Conference Series, 2026)
Periodontitis is a chronic infectious disease initiated by dental plaque biofilm and characterized by the gradual destruction of periodontal supporting tissues. As one of the primary causes of tooth loss in adults, it affects a large proportion of the glob al population and has been linked to a range of systemic diseases, creating a considerable public health burden. Conventional mechanical therapy and single -agent drug treatment remain widely used, but their clinical effectiveness is often limited, particularly in patients with persistent or recurrent disease. This review examines the pathogenesis of periodontitis and discusses the pharmacological rationale for combining metronidazole with minocycline hydrochloride. Available evidence regarding clinical efficacy, therapeutic advantages, and possible optimization strategies is also summarized, with comparisons made between combination therapy and traditional monotherapy. Current findings suggest that the combined regimen provides broader antimicrobial coverage and may achieve more consistent clinical outcomes in the management of periodontitis. Nevertheless, concerns related to long -term antibiotic use, including antimicrobial resistance and adverse reactions, remain unresolved. The limitations of the combined approach are therefore considered, and several potential directions for future research are outlined to support the development of more effective and rational treatment strategies for periodontitis.